Fatores associados à insuficiência moderada ou importante da valva atrioventricular esquerda no primeiro mês após correção de defeito de septo atrioventricular - Kozak, Marcelo Felipe (2011)
Introduction: One of the most often and important complications after surgical treatment of atrioventricular septal defects is the left atrioventricular valve insufficiency. So, this study was conducted to identify risk factors for moderate or severe left atrioventricular valve regurgitation within 30 days of surgical repair of atrioventricular septal defects at our center. Methods: This was a retrospective study in which we evaluated the results of 104 consecutive patients that were operated on at our practice between 2002 and 2010. The following associated factors were considered: age, weight, Down syndrome, grade of preoperative atrioventricular valve regurgitation, abnormalities on the atrioventricular valve and the use of annuloplasty. Patients were separated in two groups according to type of AVSD: group I (complete) and group II (incomplete – partial and transitional). Characteristics of the 53 patients of the group I: the median patient age at the time of repair was 6.7 months; the median weight was 5.3 Kg; 86.8% had Down syndrome; at the time of preoperative evaluation, there were 26 cases with moderate or severe atrioventricular valve regurgitation (49.1%); annuloplasty was perfored in 34%; abnormalities on the valve were found in 11.3% of the cases. Characteristics of the 51 patients of the group II: The median patient age at the time of repair was 4.1 years; the median weight was 13.4 Kg; 37.2% had Down syndrome; at the time of preoperative evaluation, there were 23 cases with moderate or grater LAVVR (45.1%); abnormalities on the AV valve were found in 17.6% of the cases; annuloplasty was performed in 21.6% of the patients. Results: Group I - At the time of post-operative evaluation, there were 21 cases with moderate or severe left atrioventricular valve regurgitation (39.6%). After performing a multivariate analysis, the only significant factor associated with these grades of insufficiency within 30 days of surgical correction of complete atrioventricular septal defect was the absence of Down syndrome (p = 0.03). Group II - At the time of postoperative evaluation, there were 12 cases with moderate or greater LAVVR (23.5%). During univariate analysis, only absence of Down syndrome was statistically significant (p = 0.02). However, after a multivariate analysis, none of the factors reached significance. Conclusion: Absence of Down syndrome proved to be associated with moderate or severe post-operative left atrioventricular valve regurgitation in patients with complete AVSD. However, none of the factors studied was determinant of a moderate or greater LAVVR within the first 30 days of repair of incomplete AVSD at our center.